How nursing informatization impacts nurses’ humanistic caring: a qualitative study based on Social Cognitive Theory - Yuan Liu; Yonglu Huang; Ao Huang; Xingyue Chen; Yuncai Chen; Li Li (Frontiers in Medicine, 2026)
Objective As nursing informatization continues to transform healthcare delivery, increasing attention has been directed toward nurses’ perceptions and experiences of the relationship between nursing informatization and humanistic caring. However, how nurses interpret and navigate humanistic caring within digitally transformed clinical environments remains insufficiently understood. This study aimed to explore nurses’ experiences and perceptions regarding nursing informatization and humanistic caring through the lens of Social Cognitive Theory (SCT). Methods A qualitative study using SCT-guided directed content analysis was conducted. Semi-structured interviews were undertaken with 14 clinical nurses from a tertiary Grade-A hospital in Nanjing, China, between January and March 2026. Interview data were analyzed using SCT as an interpretive framework, focusing on nurses’ experiences across the personal, behavioral, and environmental dimensions. Results Three themes and nine subthemes were identified: (1) subjective alienation and crisis (weakened motivation, changing perceptions, technology adaptation anxiety, and low self-efficacy); (2) behavioral reshaping and support (communication transformation, pattern differentiation, peer empowerment); (3) environmental double-edged sword (enhancing safety and care efficiency, systemic barriers and insufficient training). Conclusion This study provides insights into nurses’ experiences and perceptions regarding nursing informatization and humanistic caring through the lens of Social Cognitive Theory. Rather than indicating a unidirectional effect, participants described nursing informatization as a contextual factor that may facilitate or constrain humanistic caring practices through complex interactions among cognitive, behavioral, and environmental factors. Humanistic caring in digital contexts appeared to involve ongoing adaptation and negotiation between technological demands and interpersonal values. These findings may inform future discussions and practice development on how healthcare organizations can support nurses in balancing technological competence with humanistic caring within digitally transformed environments.